UPAYA MENINGKATKAN KREATIVITAS DAN KETERAMPILAN SISWA MENGGUNAKAN METODE PJBL - Adinda Taliyasalsabila; Fahrur Rosy; Achmad Mujahid Afifuddin (ELENOR: Elementary School Journal, 2024)
This research aims to improve students' creativity and skills using the PJBL method. The research was conducted at SDN Tanamera 1, Saronggi District Sumenep Regency, using the Classroom Action Research (PTK) approach which consists of planning, implementation of actions, observation, and reflection. The PJBL method improves students in developing their creativity and skills in doing project assignments, this method can also make students actively involved in creating projects. This method can help students to explore creative ideas and collaborate with peers. The results of the study show that the PJBL method is effective in improving students' creativity and skills, with an average score of 80 and above students succeed in exploring ideas and can improve their creativity and skills. The application of the PJBL method makes students more active at the time of the project. From this study, the PJBL method can be an effective solution in improving students' creativity and skills in elementary school.